Sinovac Adverse Event Following Immunization (AEFI): Correlation to Gender and History Aefi in Students - Mellybeth Indriani Louis; Merlionarsy Tammuan; Novita Wiratasia Parimpun; Gisel Pali Pasulu; Indah Puspasari Kiay Demak (Sriwijaya Journal of Medicine, 2022)
As one of the nations impacted by the COVID-19 pandemic, Indonesia adopting a vaccination policy for its population. After vaccination, there will be a chance to have an AEFI that influenced by gender and the history of AEFI from the previous vaccination. This research designed using a cross-sectional approach. Sample is taken from 365 students of Tadulako University. The questionnaire was developed using information based on Indonesia Ministry of Health and the World Health Organization. All data collected was analyzed using the Contingency Coefficient test. There was a significant relationship between gender and pain (p = 0.004, r = 0.148), redness (p = 0.041, r = 0.107), swelling at the injection site (p = 0.037, r = 0.109), cellulitis (p = 0.037, r = 0.109), and headache (p = 0.006, r = 0.143). There was a significant relationship between history of AEFI and pain (p = 0.000, r = 0.182), redness (p = 0.000, r = 0.274), swelling at the injection site (p = 0.001, r = 0.178), cellulitis (p = 0.000, r = 0.249), fever (p = 0.000, r = 0.382), myalgia (p = 0.000, r = 0.239), arthralgia (p = 0.000, r = 0.268), asthenia (p = 0.000, r = 0.254), and headache (p = 0.000, r = 0.218). More students did not get AEFI than did. AEFI was more common experienced by females and students who had no previous history of AEFI. Most of all AEFI will improve in less than a day.